Mycobacterium leprae-Specific Antibodies in Multibacillary Leprosy Patients Decrease During and After Treatment With Either the Regular 12 Doses Multidrug Therapy (MDT) or the Uniform 6 Doses MDT - Hungria, Emerith M.; Bührer-Sékula, Samira; Oliveira, Regiane M.; Aderaldo, Lúcio C.; Pontes, Maria Araci A.; Cruz, Rossilene; Gonçalves, Heitor S. de; Penna, Maria L. F.; Penna, Gerson O.; Stefani, Mariane M. A. (Frontiers in Immunology, 2018)
Leprosy serology reflects the bacillary load of patients and multidrug therapy (MDT) reduces Mycobacterium leprae-specific antibody titers of multibacillary (MB) patients. The Clinical Trial for Uniform Multidrug Therapy Regimen for Leprosy Patients in Brazil (U-MDT/CT-BR) compared outcomes of regular 12 doses MDT/R-MDT and the uniform 6 doses MDT/U-MDT for MB leprosy, both of regimens including rifampicin, clofazimine, and dapsone. This study investigated the impact of R-MDT and U-MDT and the kinetic of antibody responses to M. leprae-specific antigens in MB patients from the U-MDT/CT-BR. We tested 3,400 serum samples from 263 MB patients (R-MDT:121; U-MDT:142) recruited at two Brazilian reference centers (Dona Libânia, Fortaleza, Ceará; Alfredo da Matta Foundation, Manaus, Amazonas). Enzyme-linked immunosorbent assays with three M. leprae antigens [NT-P-BSA: trisaccharide-phenyl of phenollic glycolipid-I antigen (PGL-I); LID-1: Leprosy Infectious Disease Research Institute Diagnostic 1 di-fusion recombinant protein; and ND-O-LID: fusion complex of disaccharide-octyl of PGL-I and LID-1] were performed using around 13 samples per patient. Samples were collected at baseline/M0, during MDT (R-MDT:M1–M12 months, U-MDT:M1–M6 months) and after MDT discontinuation (first, second year). Statistical significance was assessed by the Mann–Whitney U test for comparison between groups (p values < 0.05). Mixed effect multilevel regression analyses were used to investigate intraindividual serological changes overtime. In R-MDT and U-MDT groups, males predominated, median age was 41 and 40.5 years, most patients were borderline lepromatous and lepromatous leprosy (R-MDT:88%, U-MDT: 90%). The bacilloscopic index at diagnosis was similar (medians: 3.6 in the R-MDT and 3.8 in the U-MDT group). In R-MDT and U-MDT groups, a significant decline in anti-PGL-I positivity was observed from M0 to M5 (p = 0.035, p = 0.04, respectively), from M6 to M12 and at the first and second year posttreatment (p < 0.05). Anti-LID-1 antibodies declined from M0 to M6 (p = 0.024), M7 to M12 in the R-MDT; from M0 to M4 (p = 0.003), M5 to M12 in the U-MDT and posttreatment in both groups (p > 0.0001). Anti-ND-O-LID antibodies decreased during and after treatment in both groups, similarly to anti-PGL-I antibodies. Intraindividual serology results in R-MDT and U-MDT patients showed that the difference in serology decay to all three antigens was dependent upon time only. Our serology findings in MB leprosy show that regardless of the duration of the U-MDT and R-MDT, both of them reduce M. leprae-specific antibodies during and after treatment. In leprosy, antibody levels are considered a surrogate marker of the bacillary load; therefore, our serological results suggest that shorter U-MDT is also effective in reducing the patients’ bacillary burden similarly to R-MDT. Clinical Trial Registration ClinicalTrials.gov, NCT00669643.